From Local Wisdom to Global Governance : A Meta-Analysis of Participatory Audit Models as a Pillar of BUMDes Transparency - M Irsan Nasution; Yulisfan Yulisfan; Agustina Indriani (Proceeding of The International Conference on Business and Economics, 2025)
Performance audit is a strategic instrument to strengthen transparency and accountability in the governance of Village-Owned Enterprises (BUMDes). However, current practices of BUMDes auditing in Indonesia remain limited, fragmented, and often fail to uphold the principles of good governance. This study aims to identify and synthesize the implementation of performance audits in BUMDes across various regions through a Systematic Literature Review (SLR) of 28 articles published between 2013 and 2024. Sources were obtained from Scopus, DOAJ, Google Scholar, and Garuda, with thematic analysis applied. The study identifies five core issues: weak internal audit mechanisms, limited community participation, low utilization of information technology, cultural resistance, and the role of audits in improving village economic performance. The paper proposes a participatory audit model grounded in local familial values and supported by appropriate digital tools. This hybrid model is contextually suited to promote accountability in rural areas where institutional capacity is limited but social cohesion is strong. Theoretically, this research extends the relevance of stewardship theory and participatory governance to micro-level public sector entities. Policy implications highlight the need for adaptive, community-based audit mechanisms as a foundation for accountable rural development